2004
DOI: 10.1094/cchem.2004.81.4.450
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pregerminated Brown Rice for Breadmaking

Abstract: Pregerminated brown rice (PGBR) prepared by immersing in water was used for breadmaking, and effects on the dough properties and bread qualities were studied to compare with the ungerminated brown rice (BR). The substitution of BR or PGBR for wheat flour produced smaller specific volume in bread than in the control bread without BR or PGBR along with the increasing amount of substitution. However, the bread samples containing BR or PGBR suppressed staling during storage. The improving effect was especially obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 6 publications
7
67
0
Order By: Relevance
“…At bread level, Han et al (2012) found that rice lines with low water absorption produce fresh bread with a suitable volume and firmness. Presumably, that effect could explain texture improvement observed when partial replacement of wheat flour with germinated rice and pregerminated rice (Charoenthaikij et al 2010b;Watanabe et al 2004). It is interesting to notice that WHC of the soaked sample was significantly lower than that of samples germinated for 12 h and 24 h. Again, this result could be explained due to α amylase action that takes some time to degrade intact starch granules, changing its structure.…”
Section: Flour and Flour Gel Hydration Propertiesmentioning
confidence: 95%
See 3 more Smart Citations
“…At bread level, Han et al (2012) found that rice lines with low water absorption produce fresh bread with a suitable volume and firmness. Presumably, that effect could explain texture improvement observed when partial replacement of wheat flour with germinated rice and pregerminated rice (Charoenthaikij et al 2010b;Watanabe et al 2004). It is interesting to notice that WHC of the soaked sample was significantly lower than that of samples germinated for 12 h and 24 h. Again, this result could be explained due to α amylase action that takes some time to degrade intact starch granules, changing its structure.…”
Section: Flour and Flour Gel Hydration Propertiesmentioning
confidence: 95%
“…Germinated brown rice flour (GBRF) and germinated glutinous brown rice flour have been used as functional food ingredients in breadmaking (Charoenthaikij et al 2010a(Charoenthaikij et al , b, 2012Watanabe et al 2004), due to its high content in bioactive compounds such as γ-aminobutiric acid and antioxidants such as phenolic compounds, γ-oryzanol and vitamin E (Cáceres et al 2014). The benefits of these bioactive compounds include regulation of blood pressure and heart rate, alleviation of pain and anxiety, inhibition of cancer cell proliferation, and protection for oxidative stress (Oh and Oh 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sterilization treatment of GBR-a standard process for commercialized GBR products to reduce micro-organisms-results in an increased amount of glutamic acid, alanine, and glycerin which produce a sweeter and more enhanced flavor as compared to the ordinary brown rice (Ohtsubo et al 2005). Watanabe et al (2004) showed that the substitution of brown rice or GBR for wheat flour lowered specific volume of bread more than the control bread without brown rice (BR) or GBR with increasing amounts of substitution. The improving effect was more obvious for 10 or 20% GBR than for BR.…”
Section: Uses Of Gbr and Its Productsmentioning
confidence: 99%